(untitled) (Orfeu, 2022)
This paper reports a research on the nature of the vibrato, starting from questioning its use in mechanical and stylistic terms. Thus, the objective is to formulate a systematic knowledge applied to performance in important periods of music history. Through articles and other mentions present in musical methods, a survey of observations by authors and cellists was carried out, directing an approach applied to relevant pieces of the periods in question. Therefore, it was necessary to review the literature and self-assess the use of vibrato in order to be able to adopt different types of vibrato in different musical contexts.